2022
DOI: 10.3389/fmed.2022.777443
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of Anterior Segment Parameter Measurements With CASIA 2 and IOLMaster 700

Abstract: PurposeTo compare the difference and agreement in central corneal thickness (CCT), keratometry (K), anterior chamber depth (ACD), aqueous depth (AQD), and lens thickness (LT) measured with CASIA 2 and IOLMaster 700 in patients with cataract.MethodsA total of 81 patients with cataract (81 eyes) scheduled for phacoemulsification were prospectively collected from March to May, 2020 in the cataract department of Zhongshan Ophthalmic Center, Sun Yat-sen University, including 43 males and 38 females with age of 61.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previous studies demonstrated that a larger measurement diameter rendered higher corneal irregularity, 26 , 27 so the measurement meridians or analyzed zone could have a significant impact on TK, PK, and corresponding astigmatism. The axial resolution of CASIA2, IOLMaster 700, and Pentacam AXL is ≤10 µm, 22 µm, and 50 µm, respectively, 24 , 28 , 29 which could be another possible reason for the difference in TK and PK measurements among devices.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that a larger measurement diameter rendered higher corneal irregularity, 26 , 27 so the measurement meridians or analyzed zone could have a significant impact on TK, PK, and corresponding astigmatism. The axial resolution of CASIA2, IOLMaster 700, and Pentacam AXL is ≤10 µm, 22 µm, and 50 µm, respectively, 24 , 28 , 29 which could be another possible reason for the difference in TK and PK measurements among devices.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of ACD and AQD measurements, the SW-9000 presented lower values than the MS-39, as the mean difference were − 0.10 ± 0.03 mm and − 0.10 ± 0.04 mm, while the 95% LoAs were − 0.16 to − 0.05 mm and − 0.18 to − 0.03 mm, respectively. These intervals were slightly narrower than those reported by Ruan et al, who separately assessed agreement between the IOLMaster 700 (Carl Zeiss Meditec, Jena, Germany) and CASIA 2, yielding 95% LoAs of − 0.03 to 0.24 mm for ACD and 0.04 to 0.25 mm for AQD [ 25 ]. Similar results were reported when comparing the MS-39 and the Argos (− 0.01 ± 0.03 mm) for ACD and AQD measurements, which were insufficient to produce noticeable differences in clinic [ 19 ].…”
Section: Discussionmentioning
confidence: 72%
“…Other parameters, such as the K1, K2, and mean K values showed insignifi- that a 0.5 D variation in corneal curvature was still clinically acceptable [17]. The Pentacam AXL measured diameter values of 3.0 mm and 4.0 mm for the anterior and total cornea, respectively, while IOL Master 700 obtained 2.5 mm for both of them [16].…”
Section: Discussionmentioning
confidence: 96%